Pengaruh Corporate Social Responsibility Terhadap Tax Avoidance Dengan Size Sebagai Variabel Moderating - OK Sofyan Hidayat (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2019)
Abstract: This study aims to examine the influence of the corporate social responsibility on tax avoidance with size as a moderating variable at manufacturing companies listed in Indonesia Stock Exchange. The population in this study are all manufacturing companies listed on the Stock Exchange for the 2014-2016 period. Of the 147 listed companies, 26 sample companies were selected using purposive sampling method. The data used in this study is secondary data, by downloading the financial statements from the website www.idx.co.id. Data analysis techniques used are descriptive statistics, classical assumption test, multiple regression analysis and moderate regression analysis (MRA). The partial test results using the t test show that corporate social responsibility is partially through the t test with a significance value of 0,000 <0,05 which affects tax avoidance. This means that disclosure of corporate social responsibility will affect the level of tax avoidance of a company. Size (company size) can be a moderation that strengthens the influence of corporate social responsibility on tax avoidance with a significance value of 0.001 <0.05. This means that increasing the size of the company will encourage an increase and disclosure of corporate social responsibility towards tax avoidance. Keywords :  Corporate Social Responsibility, Size, Tax Avoidance